Evaluation of hardness and dry sliding wear performance of Al/BA-silica sand composites as brake friction materials. - Sukanto Sukanto; Erwanto Erwanto; Husman Husman; Erwansyah Erwansyah; Rodika Rodika; Yudi Oktriadi; Eko Yudo; Ardiansyah Ardiansyah (Politeknik Negeri Lhokseumawe, 2026)
As many as 70 countries have banned the use of asbestos-based materials because its fine, lightweight fibers are easily inhaled by humans, causing lung cancer, particularly mesothelioma, which can be fatal. This study aims to determine the effect of a silica sand and boiler ash reinforcement alloy on the application of non-asbestos aluminum matrix composite brake pads. This research uses a powder metallurgy method with varying reinforcement weight ratios, namely 8%, 10%, 12%, and 14% by weight. The mixing process is carried out through mechanical alloying using a horizontal ball mill at 90 rpm with a BPR ratio of 10:1. Hot compaction at 300°C was varied at a pressure of 5000-5300 PSI, followed by sintering at 580°C. Density, hardness, and wear were tested using ASTM standards, which were then compared with the brake lining standard SNI-09-0143-1987. Microstructural characterization was performed using SEM to determine the extent of interlocking bonds in the composite. The results showed that the 12wt% composition at 5200 PSI produced the best properties, with a density of 2.121 g/cm³, a hardness of 93.628 HB, and a wear of 0.0193 mm³/Nm. SEM images showed more uniform interlocking bonds compared to other variations. Increasing the compaction pressure was proven to increase density, hardness, and wear resistance. Overall, this study successfully produced environmentally friendly composite brake linings based on Silica Sand Powder and Boiler Ash without using asbestos materials.